THE EFFECT OF MAULI BANANA (Musa acuminata) STEM EXTRACT ON MACROPHAGE CELL NUMBER IN PULP INFLAMATION (In Vivo Study In Male Wistar Rat (Rattusnovergicus) Teeth) - Nadia Dewi Astuti; Maharani Laillyza Apriasari; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2018)
Background: Reversible pulpitis is a mild to moderate inflammatory condition of the pulp which often given pulp capping therapy as their treatments. Commonly used or